2016
DOI: 10.1155/2016/1974972
|View full text |Cite
|
Sign up to set email alerts
|

Different Vancomycin Immunoassays Contribute to the Variability in Vancomycin Trough Measurements in Neonates

Abstract: Substantial interassay variability (up to 20%) has been described for vancomycin immunoassays in adults, but the impact of neonatal matrix is difficult to quantify because of blood volume constraints in neonates. However, we provide circumstantial evidence for a similar extent of variability. Using the same vancomycin dosing regimens and confirming similarity in clinical characteristics, vancomycin trough concentrations measured by PETINIA (2011-2012, n = 400) were 20% lower and the mean difference was 1.93 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…In addition, we found no differences in PK parameters with respect to the different vancomycin assay methods used (i.e. assays based on fluorescence polarisation or turbidimetric inhibition principles) [45]. Supportive evidence for these findings is provided in Figs.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, we found no differences in PK parameters with respect to the different vancomycin assay methods used (i.e. assays based on fluorescence polarisation or turbidimetric inhibition principles) [45]. Supportive evidence for these findings is provided in Figs.…”
Section: Discussionsupporting
confidence: 76%
“…We refer to the original studies for additional factual information. [14][15][16][17][18][19][20][21][22][23][24][25][26] Population PK analysis…”
Section: Study Populationmentioning
confidence: 99%
“…on the relevance of a given assay have also been reported in neonates.Using the same vancomycin dosing regimens and confirming similarity in clinical characteristics, vancomycin trough concentrations measured by PETINIA (2011-2012, n=400) were 20% lower, with a mean difference of 1.93 mg/l compared to COBAS (2012-2014, n=352)[78]. Furthermore, Zhao et al quantified the predictive performance of 6 published vancomycin PK models when applied to a new dataset, and observed that performance in part related to the vancomycin assay[48].…”
mentioning
confidence: 70%